The algorithm of interaction of the enterprises of fuel and energy complex in implementation with the use of alternative means of payment - O V. Baikova; D. A. Kulakov (Вестник университета, 2019)
The structure of the algorithm for building a system of payment interaction of enterprises of the fuel and energy complex has been off red. The necessity to include such intangible components as trust, business reputation, transparency of economic relations in the assessment of the value of assets of the fuel and energy complex enterprises has been highlighted. The possibility of wider application of mechanisms of non-monetary trade in the conditions of economy of “distrust” and political and economic crisis has been designated. The peculiartities of cooperation between the enterprises of the fuel and energy complex in the conditions of sanctions pressure, turning into a trade war have been revealed. The possibilities of activation and development of resource trade as one of the main factors of increasing the security of the fuel and energy complex and the Russian economy as a whole have been discovered.